STRATEGI SELF HEALING DALAM MENGELOLA STRES AKADEMIK PADA MAHASISWA TINGKAT AKHIR - Gunawan, Harry; Eko Perianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Academic stress is one of the common problems experienced by final-year university students during the thesis-writing process. Academic demands, graduation targets, family expectations, and continuous supervision may create pressure that affects students’ physical, emotional, and behavioral conditions. This study aimed to describe the forms of academic stress experienced by final-year students and the self-healing strategies they employ to manage such stress. This research used a qualitative approach with a descriptive method. Data were collected through interviews and observations involving final-year students at who were completing their theses. The data were analyzed using data reduction, data display, and conclusion drawing techniques. The findings revealed that academic stress was characterized by anxiety, fatigue, sleep disturbances, decreased learning motivation, difficulty concentrating, and a tendency to withdraw from social interactions. To cope with these conditions, students applied several self-healing strategies, namely mindfulness, gratitude, and positive selftalk. Mindfulness helped students develop self-awareness and accept their current circumstances, gratitude enabled them to maintain a positive perspective toward academic pressures, while positive self-talk strengthened their self-confidence and motivation to complete their theses. The study concludes that self-healing plays a positive role in helping students manage academic stress by improving emotional well-being, learning focus, and motivation to complete their final academic requirements.